Challenging indication of cardioverter defibrillator implantation after sudden cardiac arrest in the very young: a case series of catecholaminergic polymorphic ventricular tachycardia secondary to de novo calmodulin p.Asn98Ser. Issue 10 (5th October 2021) - Maltret, Alice; Benaich, Fatima Azzahrae; Rendu, John; Fressart, Véronique; Roux-Buisson, Nathalie; Bonnet, Damien; Denjoy, Isabelle
Abstract: Background: Calmodulinopathy is an emerging group of primary electrical disease with various, severe, and early onset phenotype. Sudden cardiac arrest (SCA)/death can be the first symptom and current medical management seems insufficient to prevent recurrences. Implantable cardioverter-defibrillator (ICD) in the young is challenging and can be harmful. Case summary: We report the management of two very young boys (aged 3.5 and 5.5 years old) who survived an SCA due to calmodulin mutation responsible of a catecholaminergic polymorphic ventricular tachycardia phenotype. In both case, SCA had an adrenergic trigger. Despite SCA, ICD implantation was denied by the parents. After thorough discussion with the family, the patients were managed with solely betablocker treatment and loop recorder implantation. At last follow-up of 30 and 23 months, respectively, there were no recurrence of any cardiac event. Discussion: The benefits of ICD implantation at a very young age must be weighed against the risk complication. In the youngest, whom recreative activities are under constant supervision, the decision, jointly made with the parents, could be to postpone ICD.